Claps and Claptrap: The Analysis of Speaker-Audience Interaction in Political Speeches - Peter Bull (Journal of Social and Political Psychology, 2016)
Significant insights have been gained into how politicians interact with live audiences through the detailed microanalysis of video and audio recordings, especially of rhetorical techniques used by politicians to invite applause. The overall aim of this paper is to propose a new theoretical model of speaker-audience interaction in set-piece political speeches, based on the concept of dialogue between speaker and audience. Research is reviewed not only on applause, but also on other audience responses, such as laughter, cheering, chanting, and booing. Research is also reviewed on other factors besides rhetorical devices, in particular, delivery, speech content, and uninvited applause. Although these analyses are based primarily on British speeches, they also include recent studies of speeches delivered in both Japan and the USA. This cross-cultural perspective, it is proposed, provides significant insights into the role of political rhetoric in speaker-audience interaction, which may be usefully conceptualized in terms of broader cross-cultural differences between collectivist and individualist societies.